A survey of babesiosis in cattle in Barangay Dao, Tuy, Batangas - Alajar, Elaine (Animo Repository, 1995)
A survey on bovine babesiosis was conducted using hematologic examination og Giemsa-stained blood smears obtained from 130 imported Brahman-Shorthorn male and female cattle ages 5 months to 10 years old. Microscopic examination generally revealed a very low parasitemia. Thin blood films from a two-year old male cattle and female cattle ages 1 1/2 and 3 years old were positive for Babesia sp. with a very low parasitemia. Blood smears from three male cattle ages 4 months, and one year and 4 years and female cattle ages 7 months, 2 years, 2 2 1/2 years, 7 years and two 1 1/2 year-olds possibly had either Anaplasma and/or Theileria sp.